The Influence of Managerial Ownership and Firm Size On Debt Policy - Lihard Stevanus Lumapow (AIBPM Publisher, 2018)
This study aims to examine and analyse the effect of managerial ownership and firm size on debt policy in the perspective of agency theory. This research uses industrial samples of manufacturing companies listed on Indonesia Stock Exchange from 2012 until 2016. Sampling technique used is purposive sampling, and data collection techniques are panel data (cross-section and time series). The analysis tool used in this research is panel data regression with fixed effect model (FEM) approach. Based on the test results show that managerial ownership has a positive and significant effect on debt policy. Company Size has a negative impact but insignificant on debt policy. The results of this study have the potential for agency conflict.